Knowledge, Attitude, and Associated Factors towards Physical Assessment among Nurses Working in Intensive Care Units: A Multicenter Cross-Sectional Study - Bikis Liyew; Ambaye Dejen Tilahun; Tilahun Kassew (Critical Care Research and Practice, 2020)
Introduction. Nurses working in the intensive care unit play an essential role in detecting patients at risk of deterioration through ongoing assessment and action in response to changing health status. Objectives. To assess knowledge, attitude, and associated factors towards physical assessment on critically ill patients among nurses working in the intensive care unit at Amhara regional state referral hospitals, Northwest Ethiopia, 2019. The research hypothesis: there is poor physical assessment knowledge, poor physical assessment attitude, and there are factors that are likely to affect nurses’ knowledge and attitude towards physical assessment providing this care to critically ill patients at Amhara regional state referral hospitals, Northwest Ethiopia, 2019. Methods. Institution-based cross-sectional study was conducted among 299 nurses from March to September 2019. A convenience sampling method was used. Data were entered by using Epi Info 7.2.2 and analyzed by using STATA 14. The result was computed by descriptive statistics and to explore predictors of knowledge, and attitude linear regression analysis models were fitted, and the adjusted unstandardized beta (β) coefficient at 95% CI was used. A p-value <0.05 was considered significant. Result and conclusion: the knowledge mean scores were 9.93 ± 2.99 [95% CI (9.59, 10.31)]. The proportion of nurse’s knowledge who score above the mean was 167 (55.9%) [95% CI (50.2, 61.5)] and below the mean 132 (44.1%) [95% CI (38.5, 49.8)]. Attitude means scores were 36.85 ± 6.21 [(36.16, 37.51)]. The proportions of nurse’s attitudes who score above the mean were 158 (52.8%) [95% CI (47.5, 58.5)] and below the mean 141 (47.2) [95% CI (41.5, 52.5)]. Regarding predictor variables, being male [β = 0.84, 95% CI (0.16, 1.52)] and taken training [β = 1.85, 95% CI (1.14, 2.56)] were factors positively associated with knowledge, whereas has taken training [β = 4.13, 95% CI (2.82, 5.44)], total years of experience [β = 0.59, 95% CI (0.25, 0.93)], and knowledge [β = 0.92, 95% CI (0.0.72, 1.12)] were factors positively associated with attitude towards physical assessment. Conclusion. Based on the result of this study, the knowledge and attitude towards physical assessment regarding critically ill patients among nurses working in intensive care units were good. Hence, training, educational support services, and awareness are recommended to encourage nurse’s knowledge and attitude towards physical assessment.